Uromyces euphorbiae on Euphorbia hirta L. from Guerreroand Michoacan (Mexico): first report - Marrufo, Gerardo Vázquez; Garcidueñas, MA Soledad Vázquez; Mukhtar, Irum (Bangladesh Journal of Botany, 2015)
During August and November, 2013, leaves of Euphorbia hirta L. were found with a rust disease in Taxco and Morelia cities in Guerrero and Michoacán states, respectively. The pustules of rust were orange - yellow to dark brown in color and were observed on lower and upper side of leaves. Necrotic red-purple or dark brown spots were also observed upper surface of leaves with pustules on the lower surface. On the basis of morphological characteristics, the rust species was identified as Uromyces euphorbiae. This is the new record of U. euphorbiae on E. hirta in Guerrero and Michoacán states in Mexico. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21619 Bangladesh J. Bot. 43(3): 375-376, 2014 (December)